2002
DOI: 10.1111/1467-937x.t01-1-00026
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Implementation and Congestion Pricing

Abstract: We consider an implementation problem faced by a planner who manages a roadway network. The problem entails both hidden information and hidden actions. We solve the planner's problem by introducing a new class of mechanisms and a new notion of implementation. The mechanisms, called price schemes, attach transfers to the available routes; they do not involve direct revelation. The method of implementation is evolutionary, requiring that players who follow any reasonable myopic adjustment process eventually lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(121 citation statements)
references
References 34 publications
1
119
0
1
Order By: Relevance
“…Guo et al (2013Guo et al ( , 2015 pointed out that the same feature can be found in the link-based models such as He et al (2010), Han and Du (2012) and Smith and Mounce (2011). The RBAP-like models with elastic demand were proposed in Sandholm (2002Sandholm ( , 2005, Yang (2007) and Li et al (2012).…”
Section: Rational Behavior Adjustment Processmentioning
confidence: 76%
“…Guo et al (2013Guo et al ( , 2015 pointed out that the same feature can be found in the link-based models such as He et al (2010), Han and Du (2012) and Smith and Mounce (2011). The RBAP-like models with elastic demand were proposed in Sandholm (2002Sandholm ( , 2005, Yang (2007) and Li et al (2012).…”
Section: Rational Behavior Adjustment Processmentioning
confidence: 76%
“…Experimental studies reveal quick convergence to inefficient Nash equilibrium in this setting (84). One solution is the use of congestion pricing that builds on our understanding of human adaptation (85). Another solution is the design of attractive alternatives to driving.…”
Section: Potential Implicationsmentioning
confidence: 99%
“…In Sandholm [30], we use this observation as the basis for an evolutionary approach to implementation theory.…”
Section: Introductionmentioning
confidence: 99%